Determination of antioxidants during the elaboration process of fermented artisanal breads - Delgadillo-Díaz, Mariana; Álvarez-Romero, Alejandra; Baleón-Ortega, Karla V.; Ortiz-Salazar, Francisco (Ecosistemas y Recursos Agropecuarios, 2023)
Due to the health problems produced by the high consumption of ultra-processed foods, it is necessary to determine the content of phenolic compounds during the elaboration of fermented artisan breads with two types of flour, a starter culture and two vegetable substrates. Five formulations were prepared: wheat flour+water (WF), whole wheat flour+water (WWF), whole wheat flour+water+beer (WWFB), whole wheat flour+water+beer+habanero chili (WWFBH) and whole wheat flour+water+beer+serrano chili (WWFBS). The WWFB bread was the most voluminous and the WF and WWF breads were the most acidic. In the different stages of the bread-making process, the amount of total phenols was higher in the WWFBS sourdough (33.74±0.03 mg GAE/100 g), while the WF bread had the highest content of total flavonoids (13.32±0.06 mg QE/100 g). Artisanal breads can be considered as a functional food to improve human health.
Keywords: sourdough; fermentation; antioxidants; functional food; artisan bread